Hierarchy of Needs, Perception and Preference for Leadership Styles within a Police Educational Institution - Alina RAUS; Mihaela HAITA; Lucreţia LAZĂR (Transylvanian Review of Administrative Sciences, 2012)
The present research investigates Maslow’s hierarchy of needs and the leadership style (perceived and ideal) in a sample of employees of a police school. The purpose of this study was to identify and propose solutions to improve the managerial activity. Based on Maslow’s theory for understanding human motivation, we developed a measurement scale for human needs. Based on Lewin’s theory of leadership style, we developed two measurement scales, one for perceived leadership and one for ideal leadership style. Agreement of judges was used to obtain valid measures. Reliable α-Cronbach coefficients were obtained for internal consistency of the measurement scales. We conducted correlational and comparative analyses between variables, regarding each professional category (police officers, police constables, civilians). The results contradict Maslow’s theoretical model for human needs, challenging the order imposed by Maslow’s pyramid. The order of the importance of needs differ from one category of personnel to another. Regardless of professional status, physiological needs are generally more significant than other needs. Comparing the perceived leadership style with the ideal style, all groups would prefer a less autocratic leadership style than it is, and more democratic than they perceive it. In addition, civilians would like a more permissive style of leadership than it is the perceived style. Perceived leadership styles are correlated differently with staff needs. Practical implications and contribution of the research are discussed.